PENERAPAN SOCIODRAMATIC PLAY UNTUK MENINGKATKAN PENGUASAAN KOSAKATA DAN MOTIVASI BELAJAR SISWA - Sheila Widya Laksmi; Niko Sudibjo (Akademika, 2018)
The mastery of English vocabulary and student motivation have received a great deal of attention in Sekolah Victory Plus (SVP) Kindergarten. English is used as the language of instruction in all Kindergarten classes. In addition, students are also encouraged to express their feelings and opinions in English. The lack of Englishvocabulary in EY 2 Jupiter students have led to a decrease in students’ motivation in using English in daily learning and conversation. Therefore, students of EY 2 Jupiter need to be equipped with a proficient English vocabulary so that they can be motivated to express opinions clearly and to understand any explanation by teachers during lessons. The aim of this research is applying sociodramatic play method to improve Englishvocabulary mastery on garment and learning motivation of students in EY 2 Jupiter. This research is a Class Action Research (CAR) with three cycles. Each cycle consists of one meeting where the subject of research is 18 students of Class EY 2 Jupiter at SVP TK Victory Plus. The data collection was done by conducting observations, tests, questionnaires and interviews and were then analyzed descriptively qualitative. Theresults showed that applying the method of sociodramatic play has led to an increase in vocabulary mastery in English and students’ learning motivation